Warlord competition - Stergios Skaperdas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Warlords compete for turf that provides them with rents and `taxable' resources but they can also offer a semblance of security within their respective territories. This article first examines two economic models of warlord competition. Because such competition takes place through the use of force or the threat of the use of force, more competition typically leads to lower material welfare as resources are wasted on unproductive arming and fighting. This is in contrast to ordinary economic models, in which typically greater competition leads to higher material welfare. Furthermore, rents from oil, diamonds, and even foreign aid crowd out production. In extreme cases this crowding out of ordinary production can be complete, whereby all economic resources can be devoted to the unproductive competition for rents. The article then reviews factors that lead either to actual war or to peace in the shadow of war. Because war is destrucrive, human beings are typically risk averse, and there exist numerous complementarities in production and consumption, we can expect peace in the shadow of war to be most often preferable by all parties. Actual war can take place because of incomplete information about the preferences and capabilities of the adversaries but also, somewhat surprisingly, when the shadow of the future is long.
Keywords: C71; C72; O17; 330; warlord competition; conflict; cooperative and non-cooperative behaviour; Krieg; Verhaltensökonomik; Theorie